2020
DOI: 10.9734/ajahr/2020/v5i130039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poultry Manure, N. P. K Fertilizer and Their Combination on the Growth and Yield of Sweet Pepper

Abstract: The objective of the experiment was to investigate the influence of organic (poultry) manure, inorganic manure (N.P.K) and their combination on the growth and yield of sweet pepper in the transitional zone of Ghana. The experiment was conducted at the research field of the College of Agriculture Education, University of Education Winneba, Mampong campus in 2017. The experiment was laid out in randomized complete block design (RCBD) which consisted of four treatments with 4 replications. The treatment groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
3
4
0
Order By: Relevance
“…This could be further explained that poultry manure contains Calcium (Ca), Magnesium (Mg), Zinc (Zn), and Manganese (Mn) in higher levels which improved the growth performance of Capsicum. Similar results were reported by [102] [103] [104] who indicated that there was a higher and more rapid release of nutrients from poultry manure-amended soil as compared to the other treatment groups [105].…”
Section: Effect Of Selected Organic (Animal) Manure On Tomato Leaf Wi...supporting
confidence: 88%
“…This could be further explained that poultry manure contains Calcium (Ca), Magnesium (Mg), Zinc (Zn), and Manganese (Mn) in higher levels which improved the growth performance of Capsicum. Similar results were reported by [102] [103] [104] who indicated that there was a higher and more rapid release of nutrients from poultry manure-amended soil as compared to the other treatment groups [105].…”
Section: Effect Of Selected Organic (Animal) Manure On Tomato Leaf Wi...supporting
confidence: 88%
“…Based on the height of plant based on the figure 3 the result shows the highest mean in the treatment is T2 (NPK green mix with chicken manure) it shows by the mean 76.55cm following by T3 59.275cm, T1 39.075cm and T0 29.7cm is the lowest. Similar to the findings of [11], the height of the plant may respond to organic fertilizers due to the release of macro and micro nutrients throughout the process of microbial breakdown. It is also a good source of organic matter, which has greater amounts of Calcium (Ca), Magnesium (Mg), Zinc (Zn), and Manganese (Mn), all of which promote growth performance.…”
Section: Figure3 the Mean Of Height Of Plant (Cm) For Different Treat...supporting
confidence: 65%
“…Maintaining soil fertility status has been seen as one of the best soil management practices that influence sweet pepper productivity. The best option to maintain soil fertility as well as higher yield is through application of organic and inorganic fertilizers (11).…”
Section: Introductionmentioning
confidence: 99%